2009
DOI: 10.1021/jp809710d
|View full text |Cite
|
Sign up to set email alerts
|

Freezing-Induced Phase Separation and Spatial Microheterogeneity in Protein Solutions

Abstract: Amid decades of research, the basic mechanisms of lyo-/cryostabilization of proteins and more complex organisms have not yet been fully established. One major bottleneck is the inability to probe into and control the molecular level interactions. The molecular interactions are responsible for the significant differences in the outcome of the preservation processes. (1) In this communication, we have utilized confocal Raman microspectroscopy to quantify the freezing-induced microheterogeneity and phase separati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
87
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 69 publications
(124 reference statements)
3
87
0
Order By: Relevance
“…Slow formation of ice allows longer time for solutes to diffuse ahead of the ice front as well as larger crystals (4). Dong et al (21) also showed that greater fraction of protein and trehalose was occluded in the ice phase when rapid freezing occurred after a high degree of supercooling. Such freezing would result in a large number of nuclei and therefore a larger number of smaller ice crystals.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Slow formation of ice allows longer time for solutes to diffuse ahead of the ice front as well as larger crystals (4). Dong et al (21) also showed that greater fraction of protein and trehalose was occluded in the ice phase when rapid freezing occurred after a high degree of supercooling. Such freezing would result in a large number of nuclei and therefore a larger number of smaller ice crystals.…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown (for a number of proteins) that as freezing proceeds and ice forms, the protein at the ice surface can undergo a marked increase in flexibility due to a loosening of the native fold and loss of secondary and tertiary structure (19)(20)(21). However, once the temperature drops further (below approximately −30°C), the mobility is lost due to the increased viscosity of the matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Gabellieri and coworkers measured dramatic decreases in phosphorescence lifetime at different subfreezing temperatures, suggesting significant conformational changes (4). Later, the same authors found that proteins substantially increased their binding to 1-anilino-8-naphthalene sulfonate (ANS), an extrinsic probe to measure solvent-exposed hydrophobic surface (16,17). More recently, Schwegman et al distinguished protein at the ice-solution interface vs. protein remaining in the interstitial solution space by fluorescence microscopy, and demonstrated their alteration in secondary structure by infrared microscopy (7).…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion of some solutes into small ice crystal also induces microscopic component and physical state heterogeneity in a frozen aqueous solution. 29 The purpose of this study was to elucidate the relationship between the miscibility of amorphous solutes in frozen solutions and their structural integrity during primary drying. The individual concentrated solute mixture and their unmixed phases in a frozen solution should possess different viscosities dependent on both composition and temperature.…”
Section: Introductionmentioning
confidence: 99%